(untitled) (Al-Academy, 2022)
The current research, tagged (visual effects in contemporary animation design), discussed visual effects, creative imagination, design idea, and the employment of animation in graphic design using typographic units. Through the methodological framework, the researcher found his research problem clear through the following question: What are the visual effects in animation design contemporary?The importance of the research is seeking to clarify the design concepts that will enhance the concept of technical development of software, the active contribution in consolidating the idea of dealing with those influences and modalities that guarantee positive results in achieving the applied aspects in their functional and aesthetic dimensions.The aim of the research is to identify the visual effects in contemporary animation design.The objective limits of research is the study of visual effects in the design of contemporary animation. The spatial limitation is the visual effects used in MBC Iraq.In the period from 2019-2021. The most important terms mentioned in the title were identified. The theoretical framework in the first topic dealt with the concept of visual effects and creative imagination in the design idea.The second topic is the employment of animation and typographic units in graphic designThe most important indicators that resulted from the theoretical framework were concluded, and the researcher did not find a previous study that was close to or converged with the current study.1- The sample appeared expressive of visual effects in animation through imagination, idea and design.2- The designers used the typographic units appropriately (image, shapes and text).3- Animation was used to establish the functional and aesthetic dimension4- The design elements and foundations had an important and effective role in distributing the design vocabulary and exploiting the dynamic space.And he drew conclusions from it1- The imagination and design ideas were clear through the role of the visual effect in the moving partitions2- The use of vocabulary and typographic elements was expressive of the intellectual and aesthetic content3- The rhythmic and dynamic organization of the elements and the method of their distribution had a role in creating a high-performance visual effectThe researcher recommended taking advantage of the results of this study to enhance the visual effects in the design of contemporary animation, which has taken a large part in the fields of making introductions and visual breaks to focus the importance of graphic design in society.The researcher suggested conducting studies on the following:1- Implications of graphic techniques on visual effects3- Functional data for visual effects in graphic design